A comparative study of the antioxidant activity of rice, wheat and spelt - Calzuola, I.; Perni, S.; Caprara, G.A.M.; Gianfranchi, G.L.; Marsili, V. (Progress in Nutrition, 2013)
In this paper the antioxidant properties of aqueous and hydroalcoholic extracts from seeds and sprout of rice, spelt and wheat, are evaluated. In order to correlate the antioxidant properties with the molecular composition, a preliminary molecular characterization was carried out by several biochemical and spectrophotometric analysis. We have found that the sprouting process strongly increases the antioxidant power, expressed as superoxide radical scavenging activity, reducing power and peroxidase activity. At the same time, the content in molecules soluble in water or ethanol/water (70/30 v/v), included the antioxidant compounds such as polyphenols and flavonoids, seems to be remarkably higher in sprouts than in seeds. In addition we found out that water is more efficient than ethanol/water in extracting active antioxidant compounds. By comparing the three tested cereals extracts, the rice was found to be, at least for what concerns the results here shown, the less active one.